2015
DOI: 10.1103/physrevb.92.054409
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity inlargeJtwo-dimensional antiferromagnets: Role of phonon scattering

Abstract: Motivated by the recent heat transport experiments in 2D antiferromagnets, such as La2CuO4, where the exchange coupling J is larger than the Debye energy ΘD, we discuss different types of relaxation processes for magnon heat current with a particular focus on coupling to 3D phonons. We study thermal conductivity by these in-plane magnetic excitations using two distinct techniques, Boltzmann formalism within the relaxation-time approximation and memory-function approach. Within these approaches, a close conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Within this picture, the transport relaxation time is the same as spin-boson scattering time and the corresponding meanfree path fits excellently the available experimental data. Further systematic extensions of our theory to include multi-phonon scattering that can influence thermal conductivity at higher temperature are briefly discussed.Finally, we emphasize an important physical constraint on the strength of spin-phonon coupling of magnetoelastic nature [31,32], which is weak in the materials of interest. While an estimate of this coupling can be made microscopically, a simple piece of phenomenological evidence for this criterion is the absence of the spinPeierls transition in real compounds down to very low temperatures.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Within this picture, the transport relaxation time is the same as spin-boson scattering time and the corresponding meanfree path fits excellently the available experimental data. Further systematic extensions of our theory to include multi-phonon scattering that can influence thermal conductivity at higher temperature are briefly discussed.Finally, we emphasize an important physical constraint on the strength of spin-phonon coupling of magnetoelastic nature [31,32], which is weak in the materials of interest. While an estimate of this coupling can be made microscopically, a simple piece of phenomenological evidence for this criterion is the absence of the spinPeierls transition in real compounds down to very low temperatures.…”
mentioning
confidence: 99%
“…Self-energy and relaxation rate.-Assuming the spinphonon coupling to be small, a conjecture discussed below in detail [32], one can consider only the second-order spin-boson self-energy in Fig. 2(a) given by…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…58 Previous studies of thermal transport in insulating magnetic materials indicated that the magnetic and thermal contributions to the thermal conductivity can be comparable. [59][60][61][62][63][64] Our main result in this work is to show that the spatially anisotropic magnetic states that can arise from strong spin-orbit coupling can dramatically affect the thermal transport, or have a rather small effect depending on the relative size of magnon and phonon thermal conductivities. In some cases, the thermal transport may help identify the symmetries of the magnetically ordered state if other measurements are difficult or problematic.…”
Section: Introductionmentioning
confidence: 98%